APPLICATION OF CORN WASTE TRICHO-COMPOST TO CHILI (Capsicum annuum L.) CULTIVATION ON PEAT - Janter Manurung; Fifi Puspita; Gunawan Tabrani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Chili (Capsicum annum L.) is one of horticultural commodities has significant economic value, however land in Riau that used for this farming have low fertility as peatland. Therefore the use of organic fertilizer that low complete material is indispensable in improving the productivity of chili, one of the organic fertilizer that is maize rubbish Tricho-compost. This research aimed to determine the effect of multiple dosage application maize rubbish Tricho-compost in enhancing the growth and productivity of chili plants on peatsoil medium. The data were analyzed statistically using analysis of variance followed by Duncan’s New Multiple Range Test (DNMRT) at 5% level and regression analysis Orthogonal. The result showed that differences in the growth and productivity of chili of several dosage of the treatment, that the provision Tricho-compost with a dosage 15-20 ton ha-1 was found to give highest circle stem, fruit weight per plant and stimulated harvesting time. Tricho-compost with a dosage 20-30 ton ha-1 was found give highest plant height, volume of root, fruit length and stimulated flowering time. Keyword : Chili, corn waste Tricho-compost, peatsoil